Assessing Macroeconomic Influences on Indian Sovereign Bond Yields: An Insight from the ARDL Bound Test Approach - Utsav .; Suresh Kumar Patra; Pramod Kumar Naik (Gospodarka Narodowa. The Polish Journal of Economics, 2024)
This paper investigates the long-term and short-term determinants of sovereign bond yields in India, a critical macroeconomic indicator closely monitored by investors and central banks. According to term structure theory, the shape of bond yields is a key economic barometer, reflecting the overall health of the economy. Using monthly time series data from April 2001 to March 2021, the study examines variables such as long-term sovereign bond yields, short-term Treasury bill yields, economic growth, inflation, the monetary policy index, exchange rates, foreign exchange reserves, gross fiscal deficit, and global Brent crude oil prices. By accounting for structural breaks under the ARDL framework, in the presence of other controlled variables, the analysis confirmed that short-term interest rates influence long-term interest rates, validating the Keynesian conjecture in the Indian context. Additionally, economic growth, the monetary policy index, and global Brent crude oil price are identified as significant drivers of long-term interest rates. These findings have important policy implications for monetary-fiscal coordination, especially in debates on the appropriate policy mix during boom-and-bust cycles. Consequently, monetary policy should be reviewed comprehensively, incorporating a broad range of macroeconomic variables.